2017
DOI: 10.1186/s12862-017-1099-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of defensins and NLRs in Arabidopsis species by different evolutionary mechanisms

Abstract: Background: Genes encoding proteins underlying host-pathogen co-evolution and which are selected for new resistance specificities frequently are under positive selection, a process that maintains diversity. Here, we tested the contribution of natural selection, recombination and transcriptional divergence to the evolutionary diversification of the plant defensins superfamily in three Arabidopsis species. The intracellular NOD-like receptor (NLR) family was used for comparison because positive selection has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 75 publications
(141 reference statements)
1
17
0
2
Order By: Relevance
“…NLRs can have an N-terminal TIR-domain (TNLs) or CC-domain (CNLs), followed by a nucleotide binding site and leucine-rich repeats. In A. thaliana, some NLRs appear to show signatures of positive or balancing selection (Bakker et al, 2006) and overall NLRs seem to show more positive selection than other defence-related gene families (Mondrag on-Palomino et al, 2017). A recent study on the total NLR complement of 65 A. thaliana accessions shows that not all NLRs show similar levels of diversity; those recognizing biotrophs are the most genetically diverse (de Weyer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…NLRs can have an N-terminal TIR-domain (TNLs) or CC-domain (CNLs), followed by a nucleotide binding site and leucine-rich repeats. In A. thaliana, some NLRs appear to show signatures of positive or balancing selection (Bakker et al, 2006) and overall NLRs seem to show more positive selection than other defence-related gene families (Mondrag on-Palomino et al, 2017). A recent study on the total NLR complement of 65 A. thaliana accessions shows that not all NLRs show similar levels of diversity; those recognizing biotrophs are the most genetically diverse (de Weyer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recombination and gene conversion have been shown to play a major role in gene family evolution for RLP family as well as other resistance gene families (Paniske et al , 1997; Mondragon-Palomino & Gaut, 2005; Mondragon-Palomino et al , 2017). Recently, it has been reported that such gene conversions, or micro recombinations, of NLR genes can also be observed between accessions of another wild Solanum sp., leading to an alternative mechanism to maintain different functional alleles (Witek et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…26 In Arabidopsis genome, it contains approximate 285 PDF and defensin-like genes. 27 Majority of Arabidopsis PDFs have eight Cys residues except for some contain only four to six. PDFs in diverse model plants and crops exhibited their involvement in the innate immune responses to fungal pathogens including Fusarium spp., Botrytis cinerea, and Verticillium dahlia, and bacteria pathogens like Pectobacterium carotovorum.…”
Section: Cysteine-rich Peptidesmentioning
confidence: 99%